Enducation Environment And The Impact Of Pandemic Covid-19 In Student Perspective - Bahagia, Bahagia; Mangunjaya, Fachruddin Majeri; Wibowo, Rimun; Rangkuti, Zulkifli (Universitas Pahlawan Tuanku Tambusai, 2021)
There are several objectives of this research, namely the COVID-19 disaster to provide natural environmental learning or education to humans, including educating people in climate-friendly and low-emission behaviour, saving energy, saving water, and recognizing the ability of the universe. Another goal is to find the social, religious and psychological impact of COVID-19 that students at Ibn Khaldun University Bogor. The research method approach used a descriptive qualitative approach. Data were collected by in-depth interviews with the class leader of semester VI students. The sample was selected through a purposive technique. The results were scrutinized carefully through triangulation and source triangulation techniques. The results show that students have the view that the arrival of COVID-19 has taught humans to behave friendly to the climate because with the presence of COVID-19, students are no longer at campus, lecturers and campus officers. This method is classified as an action to reduce glass emissions as a cause of global warming. In addition, energy and water are used very little and even at the beginning of the lockdown, these natural resources were not used, thereby educating people to save energy and water through the campus. The use of energy also causes climate problems so that it can economically reduce emissions. After that, humans are taught to live cleanly because to cope with this disaster, humans must maintain the cleanliness of the environment, themselves and places of worship. Then, the COVID-19 outbreak has a social impact because students no longer have face-to-face contact with other students, disrupt religious activities such as religion and also make students psychologically stressed